2014
DOI: 10.2139/ssrn.2515779
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Growth in Developing Asia

Abstract: In this paper we empirically explore the relationship between fiscal policy and economic growth in developing Asia. The region's overall level of taxes and government spending are substantially lower than those prevailing in advanced economies. Nevertheless, there are conceptual grounds why fiscal policy, including the composition of taxes and government spending, can have a significant effect on growth, as our empirical analysis shows. In line with economic theory, property taxes have a more benign impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Besides that regional financial allocations for spending on goods, services and capital spending can be directed at meeting the needs of life and the creation of jobs is increasingly widespread in various regions. In this case based on the results of research by Abdon, et al (2014) showed that that the composition of government spending also has a significant effect on economic growth. More specifically, our analysis indicates that shifting public spending to education will yield a sizable dividend growth.…”
Section: Discussionmentioning
confidence: 97%
“…Besides that regional financial allocations for spending on goods, services and capital spending can be directed at meeting the needs of life and the creation of jobs is increasingly widespread in various regions. In this case based on the results of research by Abdon, et al (2014) showed that that the composition of government spending also has a significant effect on economic growth. More specifically, our analysis indicates that shifting public spending to education will yield a sizable dividend growth.…”
Section: Discussionmentioning
confidence: 97%
“…A 1 percent increase in total expenditure decreases the GDP growth by 73 percent at 5% level. Baum andKoester (2011) and also retained these findings but, A Baum and Koester (2011); Oo (2019); Gechert (2015); Muravska, Martyniuk, Dluhopolskyi, Kniaz, and Podolchak (2020) and Abdon (2014) have found there is a positive linkage between the total expenditure or government expenditure and the economic growth. Similarly, the trade openness has negatively and significantly connected with GDP growth.…”
Section: Ardl Bound Testmentioning
confidence: 85%
“…The result reveals 9 percent of GDP boost due to 1 percent increase in tax revenue. Baum and Koester (2011); Muravska et al (2020) and Abdon (2014) also have investigated a positive significant relationship between tax revenue and he economic growth. The short-run coefficient of Trade openness indicates that Trade openness has a significant and positive effect on a 1 percent increase in Trade openness enhances GDP growth by 18 percent in lag 2.…”
Section: Ardl Bound Testmentioning
confidence: 99%
“…A comparison of the trends during the 1990s and 2000s indicates that the region has trailed other parts of the world in tax revenues, as they are less than half those of the OECD, as is graphically illustrated in Abdon et al (2014). The gap between developing Asia and the OECD may be explained in part by the tendency for tax revenues to rise with per capita income, but developing Asia also lags Latin America-a region with comparable income and development-in both tax and non-tax revenues (see Das-Gupta 2014 Taxes are the primary sources of fiscal revenues.…”
Section: Bmentioning
confidence: 98%
“…Among the large Asian economies in Figure 14 While taxes in general tend to deter growth, there are certain types of taxes that are considered less detrimental than others. Abdon et al (2014) simulate the impact on growth of altering the tax composition and find that reducing the reliance on income tax while raising the use of consumption and other taxes can raise GDP growth over the long run. Another finding is that raising property taxes while reducing income tax can be more beneficial to growth.…”
Section: Bmentioning
confidence: 99%